The Influence of the Creative Problem Solving Learning Model Using Inductive Learning Strategies on the Transaction Administration Learning Outcomes of Class XII Online Business and Marketing Students at SMK Negeri 1 Medan Academic Year 2023/2024 - Wulan Natasha Simanjuntak; Lenti Susanna Saragih (MultiTech Publisher, 2024)
This study aims to determine the influence of the Creative Problem Solving learning model with inductive learning strategies on the learning outcomes of transaction administration students in grade XII of Online Business and Marketing SMK Negeri 1 Medan for the 2023/2024 Academic Year. The type of research used is semi-experimental research. The experimental design used was One Group pretest-posttest design with a sample of 64 students. Data collection through learning outcome tests. The collected data was analyzed using descriptive statistical analysis and inferential statistical analysis. The result of this study is that there is a significant influence on the application of the Creative Problem Solving learning model with inductive learning strategies on the learning outcomes of transaction administration for grade XII students of Online Business and Marketing SMK Negeri 1 Medan for the 2023/2024 Academic Year with a confidence level of 95%. It is calculated with at-value of 2.886 > t. table 1.657. Where this has a significant effect, namely on the material of the sales report results. Based on this, the learning outcomes of students in the subject of Transaction Administration for Class XII students of Online Business and Marketing of SMK Negeri 1 Medan